Inflammatory responses, energy metabolism enzymes, oxidative status in Clostridium perfringens infection in broilers (Research, Society and Development, 2020)
The aim of this study was to determine whether infection by Clostridium perfringens negatively interferes with the oxidant/antioxidant status and activity of energy metabolism enzymes (creatine kinase (CK), adenylate kinase (AK) and pyruvate kinase (PK)), as well as the zootechnical performance of broilers. A completely randomized design with three treatments, with five replications by treatment, and 10 birds by repetitions was used: T1: non-infected group; T2: group infected with C. perfringens; T3: group infected with C. perfringens, and basal diet with performance enhancers (antibiotic and coccidiostatic). At 21 days of age, the birds were experimentally infected orally with 4.0 x 108 CFU/mL C. perfringens. At strategic moments during the experimental period, zootechnical data and blood samples were collected. There were no significant differences among treatments in terms of weight gain, feed intake, or feed conversion. At 20 days, heterophils counts were significantly lower in the T3 group birds than in the others. A significant reduction in the number of total leukocytes, because of the lower number of lymphocytes, was observed in groups T2 and T3 on day 34. Neutrophil and monocyte counts were significantly lower in group T3 than in group T1 on day 34. On day 42, there were significantly lower levels of total protein and globulin in birds in T3 than in T1. On day 27, PK activity was significantly higher in groups T2 and T3; similar behavior observed on day 34 when CK and PK activities in T2 and T3 were significantly higher than those of T1. AK activity was significantly higher in the serum of T3 birds than in those of the other groups at 34 days. At 41 days, CK and PK activities were significantly higher only in birds in group T3 compared to other groups. The levels of reactive oxygen species and lipoperoxidation, as well as the activity of glutathione S-transferase, were significantly lower in birds from group T3 compared to other groups at age 20 days. After a challenge with C. perfringens, there were fluctuations in the behavior of oxidative stress biomarkers; in particular, at 41 days of age, birds in T2 had elevated levels of lipoperoxidation, different from what was seen in birds in T3 that consumed feed with a performance enhancer. Preliminary results suggest that clostridiosis affects serum activity of enzymes in the phosphotransfer network, requiring compensatory enzymatic changes in an attempt to maintain energy homeostasis. In addition, the infection reduces the number of inflammatory cells and causes oxidant/antioxidant imbalance that may contribute to the pathophysiology of the disease. Además, la infección reduce el número de células inflamatorias y provoca un desequilibrio en el estado oxidante / antioxidante que puede contribuir a la fisiopatología de la enfermedad.